Wavelet based steganographic technique to protect household confidential information and seal the transmitted smart grid readings. (October 2015) - Abuadbba, Alsharif; Khalil, Ibrahim
Abstract: Smart grids have recently drawn attention because of high efficiency, reliability and sustainability. They transmit (1) periodically collected readings (e.g. watts) and (2) highly sensitive data (e.g. geometric location). However, transmission and storage of smart grid data have many security issues. This paper proposes a novel steganographic technique that guarantees (1) strong end-to-end confidentiality of the sensitive information by hiding them randomly inside the normal readings using a generated key, and (2) robust authenticity for the transmitted readings. To facilitate hiding, Discrete Wavelet Transform is used to decompose normal readings into a set of sub-band coefficients. To achieve minimum distortion, only the least featured sub-band coefficients are used. To achieve high security, a key is used to generate a random hiding order in the form of 2D matrix which allows the system to specify exact locations in the wavelet generated 2D coefficients׳ matrix to hide sensitive data. To accurately measure the distortion after hiding and retrieving the sensitive data, PRD has been used. It is clear from experiments that our technique has little effect on the original readings ( < 1 % ). Also, our security evaluation proves that unauthorised retrieval of the confidential information is highly improbable within a reasonable time.